Adolescents’ conceptualisations of depression and recovery: a discourse analysis - Dixon, Megan (2024)
Depression is most often first diagnosed during adolescence. Diagnosis rates of depression in adolescents have increased in recent years, in the context of sociocultural changes. Adolescents appear to conceptualise depression and recovery differently to mental health services, and their narratives are therefore marginalised. Adolescents’ position within social hierarchies mean they lack power to challenge the marginalisation of their narratives. The way in which depression and recovery are conceptualised have implications for the support that is offered. Conceptualisations of depression and recovery have changed throughout time and within different sociocultural contexts, suggesting that the concepts of depression and recovery are socially constructed. This contrasts with the dominant discourses drawn upon by mental health services, which often endorse the idea that depression is a mental illness resulting from underlying biological dysfunctions, and recovery is the absence of symptoms. This study was underpinned by a social constructionist epistemological stance. It aimed to analyse the discourses drawn upon by both adolescents and widely accessed websites, to conceptualise depression and recovery. Incorporating adolescents’ conceptualisations into support that is offered could reduce the power imbalance between adolescents and mental health services.